Unveiling the Impact of Experience Quality in Mediating Conversation and Co-Creation on Customer Loyalty with Currency Moderation on Disney+ Hotstar VoD Service: A Study in Bekasi Regency amid the Covid-19 Pandemic - Guntari, Anggun; Bintarti, Surya; Tanjung, Agustini; Kurniawan, Ergo Nurpatria (Jurnal Manajemen, 2024)
The Covid-19 pandemic in Indonesia is driving a shift in daily habits, which has people looking for entertainment options such as online streaming. Disney+ Hotstar, which launched in Indonesia in September 2020, quickly gained popularity and ranked second in the list of favorite apps in Indonesia in 2022. The purpose of this study is to assess how experience quality mediates conversation and co-creation on customer loyalty with moderation of Currency in Disney+ Hotstar VoD service. Conducted in Bekasi Regency, this study surveyed 108 consumers, using non-probability sampling. Correlation and regression analyses facilitated by smartPLS 3.0 were validated and confirmed their reliability. Findings show: Conversation and co-creation activities can improve consumers’ experience quality; Currency offered by Disney+ Hotstar cannot moderate conversation and co-creation on consumers’ experience quality level; Experience quality can drive customer loyalty; Experience quality level is not able to mediate conversation on customer loyalty; however, consumers’ perceived experience quality in using Disney+ Hotstar services is able to mediate co-creation on customer loyalty.